2005
DOI: 10.1007/s00264-005-0649-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of MRSA screening in joint-replacement surgery

Abstract: The aim of this prospective study was to determine the effect of screening for methicillin-resistant Staphylococcus aureus (MRSA), in patients undergoing total hip and knee replacements, on reducing hospital-acquired infections and the length of hospital stay. We included 395 patients admitted to the elective orthopaedic ward for hip and knee replacements (knee 210; hip 185) from 16 October 2000 to 15 October 2001. Group 1 included 164 admissions before 16 April 2001 when MRSA swabs were not compulsory. Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 17 publications
(18 reference statements)
0
47
0
Order By: Relevance
“…The reduction of overall SSIs ranged from 13% to 200% ( Fig. 2A) [9,11,16,20,24,26,30,43,47], the reduction of S. aureus SSIs ranged from 40% to 200% (Fig. 2B) [5,9,16,19,42,51], the reduction of MRSA SSIs ranged from 29% to 149% (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The reduction of overall SSIs ranged from 13% to 200% ( Fig. 2A) [9,11,16,20,24,26,30,43,47], the reduction of S. aureus SSIs ranged from 40% to 200% (Fig. 2B) [5,9,16,19,42,51], the reduction of MRSA SSIs ranged from 29% to 149% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…aureus detection was performed by PCR in four studies [5,19,30,40], culture in 13 studies [7,9,11,16,20,24,26,29,36,42,43,49,57], mixed methods of detection in one aggregate study [51], and unknown in one study [47]. Fifteen of the studies reported SSI reductions when only S. aureuspositive screened patients were decolonized, and eight studies [9,11,16,20,26,36,51,57] reported decreases in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations